2012
DOI: 10.1186/1471-2431-12-123
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric integrative medicine: pediatrics' newest subspecialty?

Abstract: BackgroundIntegrative medicine is defined as relationship-centered care that focuses on the whole person, is informed by evidence, and makes use of all appropriate therapeutic approaches, healthcare professionals and disciplines to achieve optimal health and healing, including evidence-based complementary and alternative medicine. Pediatric integrative medicine (PIM) develops and promotes this approach within the field of pediatrics. We conducted a survey to identify and describe PIM programs within academic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…2 More randomized controlled trials of CAM therapies are emerging, 14,15 along with new recommendations for methodologic approaches to the study of CAM. 16 CAM research and knowledge are advocated by the American Academy of Pediatrics and are being implemented for physicians in training; 17 thus, promotion of research and knowledge has become more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…2 More randomized controlled trials of CAM therapies are emerging, 14,15 along with new recommendations for methodologic approaches to the study of CAM. 16 CAM research and knowledge are advocated by the American Academy of Pediatrics and are being implemented for physicians in training; 17 thus, promotion of research and knowledge has become more feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies reported that TCM is a popular treatment in children [1, 2]. In addition, there is increasing demand of complementary and alternative medicine (CAM) treatments in the pediatric population [37]. This trend towards CAM might be explained by dissatisfaction with conventional medicine as well as positive reports from friends and family [810].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 To date, consumer interest in and use of complementary therapies has outpaced training options in pediatric integrative medicine, leaving pediatricians with a desire for more training and familiarity with resources. 8 For example, a 2012 survey of academic pediatric training programs revealed that only 16 of 143 programs reported having an integrative medicine program. 8 National initiatives to introduce pediatric integrative medicine into conventional pediatric residency training include programs such as the Pediatric Integrative Medicine in Residency program through the University of Arizona, initiated in 2012.…”
mentioning
confidence: 99%